“Spare funds” in the Public Finance Act from the perspective of the powers of the Ministry of Finance - Beata Kucia-Guściora (Prawo Budżetowe Państwa i Samorządu)
This article deals with the concept of “spare funds” – an institution of public finance law. The Author decided to look at the above-mentioned institution from the perspective of the powers of the Ministry of Finance. Hence, she analysed and evaluated current regulations, indicating successive broadening of the powers of the Ministry of Finance in this regard. In this article these powers were examined from two points of views. Firstly, the author analysed the Ministry’s authority to accept spare funds as a deposit from the public finance sector units and, consequently, to manage them. Secondly, the author indicated the competence of the Ministry to allocate available budgetary funds, as well as to manage financial assets and liabilities on the financial market. The author proves that the roles of the Ministry of Finance in the abovementioned cases differ from each other. The analysis lead to the conclusion that from a legal point of view Public Finance Act does not define precisely the above described competencies of the Ministry of Finance, leaving space for a flexible or even discretionary actions which, in economic terms, are necessary and justified.